Manejo reprodutivo em gado de corte. - CAMPOS, W. E. (2005)
ABSTRACT: The reproductive efficiency is one of the major factors contributing to the success of beef cattle production systems. To achieve satisfatory reproductive performance, it is necessary an adequate herd management, particulary the adoption of breeding season, adequate cow nutrition and adequate body condition score, evaluation of the fertility of the bulls and adoption of suitable sire: cow ratio. Moreover, other practices can enhance female reproductive performance, such as separation of calves from their dams for a period (Shang), suckling restriction, exposition of females to bulls, and selection of the most fertile animals.